Case Report: Effective treatment of dystrophic epidermolysis bullosa pruriginosa with tofacitinib - Sun, Fang; Wu, Zhenzhen; Yu, Zhenze (Frontiers in Medicine, 2025)
Epidermolysis bullosa (EB) is a heterogeneous group of hereditary skin diseases caused by mutations in structural proteins at the dermal-epidermal junction. Dystrophic epidermolysis bullosa (DEB), one of its main types, is characterized by recurrent pruritic blisters, bullae, atrophy, and scarring, often accompanied by nail dystrophy. Dystrophic epidermolysis bullosa pruriginosa, also known as epidermolysis bullosa pruriginosa (EBP), is a rare clinical subtype of DEB. In addition to the common manifestations of skin blisters and ulcers, patients with EBP also present severe pruritus. Traditional treatments for EBP have limited efficacy. In this study, we report the case of a 59-year-old male patient with EBP who showed significant improvement in skin lesions and pruritus after 10 months of treatment with tofacitinib, a pan-JAK inhibitor. This case highlights the potential of JAK inhibitors in treating EBP, although long-term safety requires further investigation.